Uma Lengge Traditional Building as a Source of Ethnomathematics-Based Mathematics Learning Implementation - Andi Hasliyati Ike Safitri; Ilham Dwi Novaldin; Supiarmo, M. Gunawan (EDUPEDIKA: Jurnal Studi Pendidikan dan Pembelajaran, 2022)
Uma Lengge is a traditional building located in the Wawo Bima district. Uma Lengge illustrates the robustness of traditional buildings that have beautiful and neat images by reflecting geometric shapes. The purpose of this research is to describe the traditional building of Uma Lengge as a source of implementation of ethnomathematics-based mathematics learning. The method used in this research is exploratory-descriptive and involves traditional building craftsmen like Uma Lengge as the main data source. Data analysis techniques used include data reduction, data presentation, and verification. The results showed that there were mathematical concepts in the form of measurement and the application of traditional arithmetic for the Bima community. In addition, there are geometrical concepts of plane and space, as well as mathematical concepts in the process of making Uma Lengge. This proves that Uma Lengge can be a source of applying ethnomathematics-based mathematics learning because good mathematics learning should have a relationship with the realities of people's lives, one of which is culture.